Sonic hedgehog promotes synovial inflammation and articular damage through p38 mitogen-activated protein kinase signaling in experimental arthritis. Issue 132 (October 2022) - Zhu, Shangling; Dang, Junlong; Shi, Yiming; Feng, Xiaoxue; Hu, Yudan; Lin, Lang; Huang, Jianlin
Abstract: Activated fibroblast-like synoviocytes (FLS) play a pivotal role in synovial inflammation and joint destruction of rheumatoid arthritis (RA). The mechanisms by which sonic hedgehog (SHH) signaling promotes RA FLS-mediated chronic inflammation and tissue damage are not fully understood. The present study aims to determine the role of SHH signaling in the pathogenesis of RA and to explore the potential mechanism(s). We found that the components of SHH signaling were highly expressed in FLS and synovial tissue from patients with RA and in the joint tissue of collagen-induced arthritis (CIA) mice. Overexpression of SHH aggravated the synovial inflammation and joint destruction of CIA and exacerbated cartilage degradation in the cartilage and RA FLS-engrafted severe combined immunodeficiency (SCID) model. Conversely, inhibition of SHH signaling significantly alleviated arthritis severity and reduced cartilage destruction caused by the invasion of RA FLS in vivo . Moreover, we found that p38 mitogen-activated protein kinase (MAPK) cascade was regulated by SHH signaling in RA FLS and the level of phospho-p38 in the joint tissue of CIA was decreased after blockade of SHH signaling. Inhibition of p38 MAPK abolished the effect of SHH overexpression on synovial inflammation and articular destruction of CIA and suppressed the aggressive properties of RA FLS, which were promoted by SHH agonist. In conclusion, our study suggests that SHH signaling aggravates synovial inflammation and joint destruction of experimental arthritis and promotes the abnormal behavior of RA FLS in a p38-dependent manner. SHH-p38 MAPK signaling could be a potential target for the treatment of RA. Highlights: FLS mediate synovial inflammation and joint destruction of RA. SHH signaling aggravates RA FLS-mediated chronic inflammation and joint damage. p38 mitogen-activated protein kinase facilitates the function of SHH signaling. Targeting SHH-p38 signaling could be a potential therapeutic strategy.